Great Expectations: A Framework for Assessing and Understanding Key Factors Affecting Student Learning of Foundational Reading Skills. Issue 155 (March 2017) - Moore, Audrey‐Marie; Gove, Amber; Tietjen, Karen
Abstract: This article addresses the evolution of the underlying theories of change in global education reform efforts between 1990 and 2015, informed by the shift in focus from access to quality and learning. We review recent data regarding how different types of donor interventions (i.e., structural or pedagogical) have contributed to improved reading outcomes and compare effect sizes over a series of intervention studies conducted from 2003 to 2015. Against this background, we present a framework for understanding how the intensity, frequency, and fidelity of the interventions as well as the enabling environments of reform affect the magnitude and rates at which reading and learning outcomes can be expected to improve. In this, we present the context for the articles that follow, identifying the program design characteristics and types of interventions that increase the likelihood of successful expansion of the interventions commonly referred to as "scaling‐up, " the ability to sustain interventions, and the value (cost effectiveness) of reading programs in low‐ and middle‐income countries.